Construção e validação de instrumento para avaliação de intervenções educativas sobre hipotermia perioperatória: associação de sistemas padronizados de linguagem - Lordelo, Daniela de Souza (2019)
Perioperative hypothermia is a problem that accounts for a proportion of postoperative complications that can be preventable and controlled. It occurs in more than 70% of surgical patients, being a concern for the health team. In view of this, the construction and validation of an Instrument for the implementation and evaluation of educational interventions containing NOC results and indicators, NIC interventions and activities, questions and answers that seek to assess knowledge about perioperative hypothermia directed to the nursing staff. lead to the improvement and better control of this problem. Objective: To construct and validate an instrument for evaluating ongoing educational interventions in NIC through criteria adapted from NOC results and indicators, aimed at perioperative prevention and control of hypothermia. Method: Methodological study of quantitative approach. The instrument was developed from the AORN, NICE and ASPAN Guidelines on perioperative hypothermia, based on the theoretical basis of the NIC and NOC and the clinical experience of the authors. The Delphi technique for content validation was used, with the participation of 12 judges in the first round and ten in the second round. For validation, a validator form elaborated in an online tool was used and considered as agreement ≥ 0. 8, which was analyzed using the content validation index and binomial test. Results: In the first round of the seven Instrument items evaluated by the judges none reached the established IVC, being reformulated after the suggested changes and submitted to the second round in which the IVC ranged from 0.8 to 1.00. Of these, the approved criterion that obtained the lowest value was “content” for items three and four, and the highest value was “objectivity” which obtained in six of the seven maximum score items (1.00) and one item with 0.90. The others obtained CVI from 0.9 to 1.0, a satisfactory score that did not indicate the need for a third round. Conclusion: The elaborated instrument was validated and can contribute to the implementation and evaluation of educational intervention with nursing in order to lead to the improvement and better control of perioperative hypothermia.